1951
DOI: 10.1063/1.1699824
|View full text |Cite
|
Sign up to set email alerts
|

Certain Refractory Compounds as Thermionic Emitters

Abstract: Several refractories of the nitride, boride, and carbide families are investigated as sources of thermionic electrons. An activation pattern qualitatively common to several of the compounds is observed. Emission data for the final state of activation are presented. Data concurrently obtained for thoria are also given for comparison. True temperature used in the Richardson equation is obtained by correction from brightness temperature. Temperature correction curves have been obtained. These curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…If such thermionic emitters are found, they may also be used as good field and thermal-field emitters. It has been suggested that some carbides are useful emitters from these points of view (Goldwater and Haddad, 1951;Eckstein et al, 1962;Ingold, 1963). We developed a new preparation method of refractory carbides of transition metals such as TaC, H E , NbC, and ZrC (Yada, 1982) and determined their emission properties from the measured brightness characteristics of the electron microscope cathodes (Yada and Shimoyama, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…If such thermionic emitters are found, they may also be used as good field and thermal-field emitters. It has been suggested that some carbides are useful emitters from these points of view (Goldwater and Haddad, 1951;Eckstein et al, 1962;Ingold, 1963). We developed a new preparation method of refractory carbides of transition metals such as TaC, H E , NbC, and ZrC (Yada, 1982) and determined their emission properties from the measured brightness characteristics of the electron microscope cathodes (Yada and Shimoyama, 1985).…”
Section: Introductionmentioning
confidence: 99%